PEMETAAN LOCATION BASED SERVICE (LBS) WISATA BENGKULU BERBASIS ANDROID - Lia Astari; Khairil Khairil (UNIVED Press, 2014)
Evolvingcurrent technologi essuch asmobile technology, its One Android smartphone technology, with the advancement of technology information system layout Travellocations, hotels, Bim can search through android smartphone. The pur-poseof this research hisaimed tomake the mapping location-based services (LBS) android based bengkulu tour. This ap-plication can determine the location of the location any where Tourism, Hotels, Bim which has been established. The application is built Android using Java programming ADT software Bundlein which there is Eclipse aseditor java pro-gramming language, as a pluginfor the Eclipse ADT, and the SDK for Android based application development tinterests. The end result ofthis research hisamapping application layout tourist sites, hotels, bim-based android. Location Infor-mation System Location of Tourism, Hotel and Bim is easier toget information tersebut.Keyword: Location mapping, android, Eclipse Android Developer tools